Report of the Working Group on Agricultural Development in Eastern and North - Eastern India for the Tenth Five Year Plan(2002-2007) - Planning Commission (Planning Commission, Government of India, 2001)
The Report of the Working Group on Agricultural Development in Eastern and North Eastern India for the Tenth Five Year Plan (2002–2007), chaired by Shri Bhaskar Barua, provides a comprehensive assessment of the region’s agricultural potential, constraints, and development strategies. Despite India’s overall progress in achieving food self-sufficiency, the Eastern and North Eastern regions have lagged in agricultural growth due to historical, infrastructural, socio-economic, and technological deficits. The report identifies key gaps in productivity, resource utilization, rural infrastructure, and market linkages, emphasizing the need for a paradigm shift in planning that places agriculture and allied sectors at the core of regional development. The vision outlined includes income enhancement through multiple livelihood opportunities, sustainable agriculture via integrated farming systems, efficient natural resource management, capital formation, and harnessing frontier technologies. Specific strategies proposed include eco-regional technology missions, rice-based and diversified farming systems, utilization of rice-fallow areas, on-farm water management, agro-forestry, organic farming, bio-villages, promotion of horticulture and floriculture, medicinal and aromatic plants, livestock and dairy development, fisheries, post-harvest management, and enhancing access to institutional credit. Emphasis is placed on participatory micro-planning, decentralization, women’s empowerment, youth engagement, and novel extension delivery systems. The report further highlights the export potential and market opportunities, advocating coordinated action among governmental, non-governmental, and private sector actors to improve productivity, competitiveness, and rural livelihoods, while addressing regional disparities and ensuring equitable and sustainable agricultural development.
Government of India Planning Commission August, 2001
Keywords: Agricultural Development; Eastern India; North Eastern India; Farming Systems; Livelihood Opportunities; Productivity Gap; Eco-Regional Technology; Organic Farming; Horticulture; Animal Husbandry; Fisheries; Rural Infrastructure